The right to self-determination as a strategy to dispute the legal field. / El derecho a la autodeterminación como estrategia para la disputa en el campo jurídico. - RUBIO MEDINA, Edwin (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article proposes several reflections on the development of human rights, in particular the right to self-determination. As a framework of interpretation, I claim that self-determination has had drastic perspectives and it can constitute an important instrument to support the emancipation process promoted by social movements. The methodology developed was grounded on a theoretical, historical and bibliographic analysis, taken into account the main milestones of the legalization of the right to self-determination. In that sense is illustrated the case of the global indigenous movement, which reinterpreted the notion of self-determination through the Bolivian Constitution and the concept of Sumak KawsayRESUMEN El presente artículo lleva una reflexión crítica-propositiva de los derechos humanos y el derecho a la autodeterminación. Como marco de interpretación propongo que el derecho a la autodeterminación ha generado diferentes interpretaciones y puede constituirse en un baluarte para los procesos de emancipación social promovidos por distintos movimientos sociales. La metodología desarrollada consistió en un análisis teórico, histórico y bibliográfico de los principales hitos de la legalización internacional a la autodeterminación. En este sentido presento como ejemplo el caso del movimiento indígena global, el cual reinterpretó la noción de autodeterminación a través del concepto de la constitución boliviana Sumak Kawsay.